ANALISIS PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH SERTA KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KOTA TOMOHON - JULITA KRISTI PONDAAG; WILLIAM AGUSTINUS AREROS; SONNY GERSON KAPARANG (JURNAL ADMINISTRASI BISNIS, 2016)
Abstract. The purpose of this study was to determine and analyze the contribution of local taxes and fees for revenue Tomohon. The method used in this study is a blend of quantitative and qualitative analysis. The results of the analysis indicate that the acceptance of local taxes and levies have an impact on income reception area. Within three years of taxes and levies contributed significantly to the income of Tomohon. In the future expected tax contribution to the development of the higher Tomohon city. Therefore, Tomohon city government should be able to provide insight to taxpayers about the importance of paying taxes to the development and progress of the region. Keywords: Regional Taxes, Levies, Regional Revenue